Map of the United States of America. (1899)
Map shows railroads, state and territorial boundaries, major cities and towns; Klondike district, gold fields, and mineral resources on inset; railroads, counties for Maine on verso; railroads, cities, and towns for British Columbia on verso. Relief shown by hachures and spot heights. Scale [ca. 1:9,400,000].